The relationship between abusive supervision, psychological ownership, and quality of nursing care: The mediating role of job satisfaction. Issue 4 (2nd August 2021) - Sharif Nia, Hamid; Pahlevan Sharif, Saeed; She, Long; Sivarajan Froelicher, Erika; Kaveh, Omolhoda; Rahmatpour, Pardis
Abstract: Purpose: This study tested a hypothetical model to evaluate the relationship between job satisfaction, abusive supervision, and psychological ownership with the quality of nursing care. Design and Methods: In this cross‐sectional study, a sample of 300 nurses from two public hospitals in Iran was selected. Exploratory factor analysis was used to assess the measurement model and the proposed structural model. Findings: There was a significant negative relationship between abusive supervision with nurses' job satisfaction and quality of nursing care. A positive relationship between psychological ownership with nurses' job satisfaction and quality of nursing care was observed. Practice Implications: Given the importance of nurses' job satisfaction, nursing managers can enhance the quality of nursing care by providing a favorable work environment for nurses.